2020
DOI: 10.1080/20008198.2020.1753942
|View full text |Cite
|
Sign up to set email alerts
|

Impact of childhood maltreatment on obsessive-compulsive disorder symptom severity and treatment outcome

Abstract: Background : Preliminary evidence suggests childhood maltreatment to play a causal role in the development and maintenance of obsessive-compulsive disorder (OCD). However, both the effect of childhood maltreatment on the course of OCD treatment and the role of specific subtypes of maltreatment remain largely unknown. Objective : This study aimed to investigate the relationship between childhood maltreatment and the severity and time course of OCD symptoms within a clinical sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 49 publications
0
14
1
Order By: Relevance
“…They pointed out that a significant correlation between severity of OCD and intolerance of uncertainty. Boger et al [20] reached the same results. However as in the all this kind of studies, their sample size is so small and the intermediate variables could not be controlled so the results of the studies are far from being scientific evidence.…”
Section: Obsessive Compulsive Disorder As a Way Of Coping With Adversity And Uncertaintymentioning
confidence: 53%
“…They pointed out that a significant correlation between severity of OCD and intolerance of uncertainty. Boger et al [20] reached the same results. However as in the all this kind of studies, their sample size is so small and the intermediate variables could not be controlled so the results of the studies are far from being scientific evidence.…”
Section: Obsessive Compulsive Disorder As a Way Of Coping With Adversity And Uncertaintymentioning
confidence: 53%
“…Additionally, later analyses of the cut-offs also showed that significantly more children living in foster families showed conspicuous compulsive behavior. Several new studies have shown that there is a connection between OCD and the experience of maltreatment in the childhood [ 60 , 61 ]. To give an example, a new Canadian health survey with 25097 participants has shown that 72% of people with OCD hat experienced some form of childhood maltreatment [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“… 64 It also has been directly linked to higher OCD symptom severity. 65 However, in individuals with OCD and a history of childhood maltreatment, unacceptable obsessional thoughts and responsibility for harm may be critical to this connection. 61 Emotion regulation has also been proposed as a potential underlying mechanism of OCD-related suicidality, due to a critical disruption of these abilities following an adverse event.…”
Section: Methodsmentioning
confidence: 99%